HUBUNGAN PERSEPSI POTENSI KORUPSI DENGAN INTEGRASI BISNIS, INTEGRASI PUBLIK DAN SISTEM INTEGRASI LOKAL (ANALISA DATA DARI SURVEI PERSEPSI KORUPSI) - Siregar, Santi Lina (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Corruption Potential is a condition that allows corruption to occur. This paper aims to see whether perceptions of potential corruption have a relationship with business integrity, public integrity, local integrity systems, and economic growth. The research method used is descriptive analysis by looking at the relationship between variables using rank and Rank Spearman test. The results indicate that perceptions of potential corruption have links with local integration systems, local integration systems have a relationship with the perception of business integrity, and the perception of integrity has a business relationship with public integrity. Thus there are findings that the eradication of corruption can not be initiated from public integrity but must be initiated by the improvement of a clean system.Keywords: Corruption Potential, Corruption Perception Survey, Business Integration, Public Integration, Local Integration System.